La Perrita Que Le Encantaban Las Tortillas = The Dog Who Loved Tortillas - Saenz, Benjamin Alire; Garcia, Geronimo (El Paso, Tex. : Cinco Puntos Press, 2012)
When Gabriela and her brother Little Diego get a puppy named Sofie, they fight over who she belongs to, but when Sofie gets very sick they find the answer.
Keywords: Dogs -- Fiction